A hybrid metaheuristic routing algorithm for low-level picker-to-part systems. (October 2021) - Bottani, Eleonora; Casella, Giorgia; Murino, Teresa
Highlights: The minimization of the travel distance of pickers in manual warehouses is proposed. A model in MATLAB reproduces the Harmony Search (HS) algorithm applied to picking. The model performance is tested on 25 scenarios with 30 pick lists (750 simulations) A comparison with heuristic routing policies is made to validate the results obtained. The HS algorithm is generally able to provide better results than other algorithms. Abstract: An application of an adapted Harmony Search (HS) algorithm is proposed in this study in order to minimize manual warehouses' pickers travel distance. Firstly, the distance matrix has been determined through a hybrid algorithm, and then HS is used to compute the pickers' travel distance, developing a MATLAB® simulation model. This model performance is tested on twenty-five scenarios, resulting from variable length of the order pick lists and different manual storage configurations. Thirty picklists are evaluated for each scenario, for a total of 750 simulations. The results provided by the algorithm, compared with those returned by a metaheuristic algorithm and two heuristic routing policies, suggest that HS provides better outputs results than the remaining algorithms. The algorithm is also very efficient from a computational perspective; as order picking is an operational decision, the short computational time allows the pickers route to be defined even in real-time if needed.